Tree growth, mortality and recruitment in four inland tropical dry evergreen forest sites of Peninsular India (Biodiversitas Journal of Biological Diversity, 2017)
Pandian E, Parthasarathy N. 2017. Tree growth, mortality and recruitment in four inland tropical dry evergreen forest sites of Peninsular India. Biodiversitas 18: 1646-1656. Tree diversity was re-inventoried after a decade (2003-2013) for assessing growth, mortality and recruitment rates in four inland tropical dry evergreen forest sites on the Coromandel Cost of India. Four 1-ha square plots (100 m x 100 m) were established in 2003 in four tropical dry evergreen forest sites, i.e. Araiyapatti (AP), Karisakkadu (KR), Maramadakki (MM) and Shanmuganathapuram (SP). These four plots were re-inventoried in 2013 to determine decadal changes in tree diversity. All trees â‰¥10 cm girth at breast height (gbh) were measured at 1.3 m from the ground level. The initial inventories in 2003 recorded 57 tree species, whereas, in 2013, 56 species were recorded from 46 genera and 26 families. Tree basal area declined by 6.2 % and 3.4 % in sites KR and SP respectively, whereas in the other two sites it increased; AP (1.6 %) and MM (16.8 %). The mean growth rate of trees (â‰¥ 10 cm gbh) in four tropical dry evergreen forest sites ranged from 0.68 to 1.52 cm yr-1. High recruitment rate was recorded in less disturbed sites KR (21.8 % yr-1) and MM (11.5 % yr-1), while the moderately disturbed sites showed 9.1% yr-1in site AP and 5.1 % yr-1 in site SP. Mortality rates were 23.5 and 45.7% yr-1 in highly disturbed sites AP and SP respectively.
Keywords: Forest dynamics; mortality; recruitment; tree growth; tropical dry evergreen forest